Practicum-Based Inquiry Learning to Improve Learning Outcome of Students at Senior High School - Kamalliansyah Walil; Indah Suryawati; Nurul Akmal (STAI Hubbulwathan Duri, 2021)
This study aims to determine the improvement of learning outcomes before and after being taught by practicum-based inquiry learning. Moreover, to analyze students' science process skills through practicum-based inquiry learning at SMA Negeri 1 Sukamakmur, Aceh Besar, Indonesia. The research was started with the preparation of learning outcomes test instruments and scientific process skills observation sheets. Furthermore, the two instruments were validated by two expert validations. The data analyzed are quantitative and qualitative. Quantitative data is in the form of learning outcomes data, while qualitative data from this study are from observations of science process skills. Learning outcomes data using statistical tests used to process learning outcomes data is the average difference test, namely the t-test. In contrast, the Science Process Skills data uses the percentage formula. This research is pre-experimental research with a one-group pretest and post-test design. Data analysis of learning outcomes was carried out using paired t-test, while science process skills used the percentage formula. The results showed that the average pretest score of students in understanding the material was still low, while the average post-test score was much better. The pretest value is 47.83, while the post-test value is 76.28. In addition, normalization and homogeneity of data are also necessary. Based on the calculations, the normal results were obtained at the X-hit 3.85 and the post-test value of the normal data with the X-hit value 4.77. After the data is normally distributed, it is necessary to test the homogeneity of the data. If you look at the data homogeneity, it is found that the experimental and control classes are homogeneous with an F-hit of 1.25, which tells that the class has the same or homogeneous variance. The value of thit = 4.03 ttable = 2.1. Thus it can be concluded that the cognitive learning outcomes of students taught using practicum-based inquiry learning are higher than conventional methods. This research shows that practicum-based inquiry learning does improve not only cognitive learning outcomes but also effective ones.